A case of neuronal intranuclear inclusion disease (NIID) presenting with hydrocephalus-like clinical features: case report - Yonghong Wang; Yongxiang Li; Wei Pan; Yuezhen Shen; Junxia Li; Ying Liu; Yuhua Peng; Shulai Zhu (BMC Neurology)
Abstract Background Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disorder characterized by the presence of inclusions within the nuclei of various cell types. The clinical manifestations of patients with NIID are diverse. Here, we present the case of a patient with NIID whose clinical presentation and magnetic resonance features closely resembled those of hydrocephalus. Case presentation The patient was 71-year-old woman with no significant family history. Seven years previously, she began to experience tremors in both hands, which occurred at rest and while holding objects; this was accompanied by urinary incontinence. Four years previously, she developed weakness in both lower limbs, an unstable gait, and dizziness. Over the past year, she noticed stiffening at the root of her tongue, cognitive decline, and slower reaction times compared to her previous state. Upon admission, cranial magnetic resonance imaging (MRI) revealed hydrocephalus-like changes. A cerebrospinal fluid drainage test returned negative results. The patient presented with tremors and urinary incontinence. Physical examination indicated pupillary constriction, and electromyography suggested peripheral neuropathy. Genetic testing revealed 91 GGC repeats in the NOTCH2NLC gene, indicating abnormal expansion. The final diagnosis was NIID. We provided symptomatic treatment for the tremor and cognitive impairment, but there was no significant improvement in the clinical symptoms. Conclusions Our case suggests that when a patient presents with clinical symptoms and MRI findings resembling hydrocephalus, the possibility of NIID should be considered, especially in the presence of tremors and autonomic symptoms.